Schwannoma of False Vocal Cord - A Rare Entity - Deo, Arju; Maharjan, Daisy; Karna, Alina (Nepal Journal of Health Sciences, 2021)
Laryngeal Schwannoma is rare comprising 0.1 – 1.5% of all benign laryngeal tumors. The most common site in larynx is aryepiglottic fold followed by arytenoids, ventricular folds, and vocal cord. Patients present with the symptoms of hoarseness, dysphagia or globus sensation. We present a 33-year-old male with supraglottic schwannoma who experienced hoarseness of voice for three months. The patient underwent micro laryngeal surgery and submucosal solid tumor of false vocal cord was removed. Postoperative recovery was uneventful and after one month of follow up the patient was improving with no hoarseness of voice.